Peran Tokoh Agama dalam Mengembangkan Pengetahuan Keislaman Warga Muallaf - Syamsulda; Ruhaya, Besse; Syamsuri; Qamar, Syamsul; Rusmin B, Muhammad (Faculty of Tarbiyah and Teacher Training, 2024)
This study aims to describe religious figures' role in developing converts' Islamic knowledge. This type of research is qualitative. The data sources in this study are religious figures and converts in the Muallaf village, Darussalam hamlet, Lembang district, Pinrang regency. The data collection techniques used are observation, interview, and documentation techniques. The research instruments are observation and interview guidelines. Data analysis techniques include data reduction, data presentation, and drawing conclusions and verification. Data validity testing is carried out by data triangulation testing. This study's results state that religious figures' role in developing Islamic knowledge for converts in the Darussalam hamlet, Lembang district, Pinrang regency is good. There are supporting and inhibiting factors for religious figures in developing Islamic knowledge for converts. However, there are also solutions that religious figures can provide for inhibiting factors. This research implies that religious leaders should always improve the Islamic knowledge of converts in the Darussalam hamlet, Lembang sub-district, Pinrang regency through methods that make it easier for converts to learn so that they can easily learn Islam and as input to the convert village.